GENETIC DIVERSITY AND CHARACTERIZATION OF COMMON BACTERIAL BLIGHT RESISTANCE IN COMMON BEAN (Phaseolus vulgaris L.) IN NORTHERN NIGERIA USING GENOME-WIDE ASSOCIATION STUDIES - Adi, Bem Alexender; Sani, Yusha'u El-Sunais (FUDMA JOURNAL OF SCIENCES, 2025)
This research aimed to identify and characterize genes associated with Common Bacterial Blight (CBB) resistance in Nigerian common beans using Genome-Wide Association Studies (GWAS). A total of 200 common bean accessions, along with their phenotypic data, were used for the study. The accessions were genotyped using the BARCBean6K_3 Infinium BeadChips, and SNPs were called using GenomeStudio V2011.1. A filtering process was applied to remove SNPs with a high missing data rate (>10%), a high heterozygosity rate (>10%), or a low minor allele frequency (<5%). This process resulted in 3385 SNPs, which were then analyzed using the FARM-CPU statistical model. Significant SNPs were further analyzed for candidate genes within 50 kilobases (kb) on either side, using the Andean whole-genome reference sequence Pvulgaris442_v2.1. The study found that SNP density within 1 Megabase (Mb) regions varied significantly across chromosomes 2, 3, 4, 7, 8, and 11, indicating the presence of genes likely associated with CBB resistance. Significant SNPs linked to CBB resistance were identified on chromosomes 1 (S1_592430 and S1_51813720), chromosome 2 (S_497752 and S_23503780), chromosome 5 (S_29125559), chromosome 7 (S_48915121), and chromosome 9 (S_20265703 and S_35923756). Candidate genes in these regions were associated with defense-related pathways, including nucleotide-binding site leucine-rich repeat (NBS-LRR) proteins, kinases, and transcription factors involved in pathogen detection and stress response regulation. The findings of this research deepen our understanding of the genetic basis of CBB resistance in common beans and offer potential applications for other crop species and regions.